2001
DOI: 10.1093/ndt/16.8.1607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic renal failure on the expression and function of rat intestinal P‐glycoprotein in drug excretion

Abstract: Intestinal secretion of rhodamine 123 is mainly mediated by P-glycoprotein. It was reduced in rats with chronic renal failure, reflecting reduced intestinal drug elimination via a decrease in P-glycoprotein transport activity rather than via protein underexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 25 publications
7
28
0
Order By: Relevance
“…Veau et al (2001) have demonstrated previously a reduction in the activity of Pgp in CRF rats. However, they did not detect any difference in protein expression of intestinal Pgp in CRF rats.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Veau et al (2001) have demonstrated previously a reduction in the activity of Pgp in CRF rats. However, they did not detect any difference in protein expression of intestinal Pgp in CRF rats.…”
Section: Discussionmentioning
confidence: 77%
“…Pgp function was evaluated by the in vitro transport of Rho-123 (Sigma) across rat everted gut sacs as described previously (Barthe et al, 1999;Veau et al, 2001). The ileum (where Pgp is more abundant) was removed and cut into 6-cm-long segments.…”
Section: Genementioning
confidence: 99%
See 1 more Smart Citation
“…Also, P-glycoprotein transporter is an energy-dependent multidrug efflux pump that serves to protect against toxic compound accumulation by transporting such substances, which include statins, into the intestinal lumen, bile, and urine. Cyclosporine but not tacrolimus has been shown to be a potent inhibitor of P-glycoprotein (213,214), and its transport activity seems to be reduced in rats with chronic renal failure (215). Clearly, this inhibition of hepatic uptake and enteric efflux of statins in cyclosporine-treated patients could increase risk for toxic accumulation.…”
Section: Safety Of Lld In the Ckd Populationmentioning
confidence: 99%
“…The transport of Rh-123, vinblastine, FD-4, and the rhizoma coptidis alkaloids across rat everted sacs was evaluated as described (Veau et al, 2001), with modifications. In brief, 12 rats were used in each everted gut sac experiment.…”
Section: Lc/ms/ms Analysis Of Rhizoma Coptidis Alkaloidsmentioning
confidence: 99%